2013
DOI: 10.1088/1674-1056/22/6/060501
|View full text |Cite
|
Sign up to set email alerts
|

The vibron dressing in α-helicoidal macromolecular chains

Abstract: We present a study of the physical properties of the vibrational excitation in α-helicoidal macromolecular chains, caused by the interaction with acoustical and optical phonon modes. The influence of the temperature and the basic system parameters on the vibron dressing has been analyzed by employing the simple mean-field approach based on the variational extension of the Lang-Firsov unitary transformation. Applied approach predicts a region in system parameter space where one takes place an abrupt transition … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…1 and 2. Obtained results appear to be consistent with the predictions of our earlier work concerned with the vibron self-trapping in the alpha-helix and two parallel chain structures [14,18]. Briefly, we found that the system parameter space is divided on two characteristic areas: in the first area vibron dressing is a continuous function of the coupling constant S for fixed values of T and B.…”
Section: Physical Foundation Of the Problemsupporting
confidence: 89%
“…1 and 2. Obtained results appear to be consistent with the predictions of our earlier work concerned with the vibron self-trapping in the alpha-helix and two parallel chain structures [14,18]. Briefly, we found that the system parameter space is divided on two characteristic areas: in the first area vibron dressing is a continuous function of the coupling constant S for fixed values of T and B.…”
Section: Physical Foundation Of the Problemsupporting
confidence: 89%
“…In order to facilitate an analytic treatment, we assume the equal dressing fraction for all phonon modes introducing the new variational parameter-dressing fraction (δ) taking [5,22,32]…”
Section: Theoretical Modelmentioning
confidence: 99%
“…The further calculations should be made in terms of two independent dimensionless parameters: adiabatic parameter B , determining the character of the lattice deformation engaged in the polaron formation and coupling constant S [2,3]. In the case when quasiparticle interacts with non dispersional optical phonon modes, they become: For the same values of the system parameters, relative diffusivity (i.e.…”
Section: Model Hamiltonian and Polaron Picture In Macromolecular Chainmentioning
confidence: 99%
“…All these processes involve protein molecules as mediators of the long distance energy transfer. According to recent research [2,3,4], vibron self-trapping (ST) in protein macromolecules, and other biological macromolecular chains (MCs), will result in creation of partially dressed rather than fully dressed small polaron state (for solitonic nature of energy ST when the potential well may induced by local distortion of the molecular crystals, see e.g. [5]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation